Comparison of the Effectiveness of Discovery Learning and Problem-Based Learning Models in Volleyball-Based Physical Education Learning (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to compare the effectiveness of the Discovery Learning (DL) and Problem-Based Learning (PBL) models in improving basic volleyball technical skills in students at SMP Negeri 2 Makassar. The study used a quasi-experimental design with two treatment groups, each consisting of 20 students. The measurement instrument was a basic technical skills test covering underhand passing, overhand passing, and serving. Data analysis was conducted using paired sample t-tests, independent sample t-tests, and effect size calculations. The results showed that both learning models significantly improved basic volleyball technical skills (p < 0.05). In the Discovery Learning group, the average score increased from 14.85 in the pretest to 22.30 in the posttest, a difference of 7.45 points. Meanwhile, the PBL group experienced a greater improvement, from a pretest average of 15.10 to 25.15 in the posttest, a difference of 10.05 points. An intergroup comparison using an independent sample t-test yielded a p-value of 0.003, indicating a significant difference in improvement between the two learning models. The effect size also confirmed this result, with PBL having a stronger effect with d = 2.03 (very large), while DL achieved d = 1.56 (large). Overall, this study concluded that while both models were effective, Problem-Based Learning was superior in improving basic volleyball technical skills. These findings recommend the implementation of PBL as a relevant alternative learning model in physical education at the junior high school level.